Perencanaan Saluran Drainase Jalan Lingkar Utara Subang - Kuni Saadati; Eilif Kurnia Deda Djamres; Januari Yanto (Journal Information Technology Engineering and Science (JITES), 2025)
Drainage is a crucial aspect of road construction, as without drainage, runoff from the road surface will remain stagnant for a long time, leading to rapid damage to the surface. Knowledge of road drainage systems will significantly increase the road's lifespan. Considering the importance of road drainage, a calculation of the road drainage system for the North Ring Road in Subang Regency is required. The flood discharge used for the road drainage system design is calculated using the rational equation. The two main components of this method are the time of concentration and the intensity of rainfall. Therefore, in this calculation, the planned flood discharge for the drainage channel is calculated using the rational equation. The channel is designed to have sufficient dimensions to accommodate the planned discharge from the hydrological calculations, with a certain base slope to ensure smooth water flow without causing sedimentation or erosion. This results in a typical road drainage image that illustrates the shape and main components of the planned channel system to efficiently drain surface water from the road to the final drainage channel.